Submorphemic Word Formation in Lithuanian Neology: Patterns in the Formation of Lexical Blends - Brazaitytė, Gabrielė (Lietuvių kalba, 2025)
The article examines the formation patterns of lexical blends – words created by non-morphemically combining at least two words – in the Lithuanian language. Although traditionally blends are not considered derivational formations, the phonetic regularities identified in this study suggest that blends are systematically motivated units that may be integrated into the general word-formation system. The aim of the study is to structurally analyze lexical blends recorded in the Database of Lithuanian Neologisms and to determine the phonetic regularities that govern their formation. The study reveals that blends are typically formed in two ways: through overlap (when phonemes from both source words coincide) and through concatenation (when the components are joined without phonemic overlap). The formation of blends is motivated by similarity to a prototype word – most often the second component – which determines the syllable count, stress pattern, and syllable structure of the blend. Regularities in breakpoint placement – the non-morphemic boundary where the two source words are joined – were also identified: the first source word most frequently breaks at the onset-nucleus boundary, while the second breaks at the syllable boundary. These findings suggest that blends are formed in accordance with Lithuanian phonotactic constraints and with the aim of preserving recognizability. Breakpoints at the nucleus-coda boundary are avoided, as the nucleus and coda form the rhyme, which is crucial to a word’s sound and recognizability. Thus, although lexical blends lack the morphemic structure typical of traditional word-formation, the study demonstrates that they follow consistent phonetic patterns and should therefore be considered a potential part of the word-formation system.